2005
DOI: 10.1136/ijgc-00009577-200505000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic exenterations for gynecological malignancies: twenty-year experience at Roswell Park Cancer Institute

Abstract: The objective of this study is to review the experience with pelvic exenterations for gynecological malignancies at our cancer institute. Charts of 48 women who underwent a pelvic exenteration between January 1980 and December 1999 were reviewed, and several outcomes were analyzed. Majority of patients had received prior radiation therapy. The median survival was 35 months, and the disease-free survival was 32 months. Mortality from the procedure was 4.2%. Early and late postoperative complication rates were 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 9 publications
2
25
0
1
Order By: Relevance
“…Most oncologic centers in both countries do not define an age threshold. 9,10,12,13,15 The impact of the tumor size of the recurrent tumor is discussed controversially. 2,10,13,16 Tumor-involved para-aortic lymph nodes or peritoneal tumor is generally seen as a contraindication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most oncologic centers in both countries do not define an age threshold. 9,10,12,13,15 The impact of the tumor size of the recurrent tumor is discussed controversially. 2,10,13,16 Tumor-involved para-aortic lymph nodes or peritoneal tumor is generally seen as a contraindication.…”
Section: Discussionmentioning
confidence: 99%
“…2,10,13,16 Tumor-involved para-aortic lymph nodes or peritoneal tumor is generally seen as a contraindication. 7,11,12,16,24 However, 21% of German institutions continue surgery despite the presence of distant metastasis, and 86% continue in patients with positive intraperitoneal cytology.…”
Section: Discussionmentioning
confidence: 99%
“…Although some smaller studies did not find a prognostic significance of the progression-free interval from the primary treatment in patients after pelvic exenteration,29 most authors reported a substantially better prognosis in cases with a long interval from the initial treatment 3 30. Marnitz reported a 17% 5-year survival in patients who experienced recurrence in <2 years after the initial treatment, 28% for patients with disease recurring between 2 and 5 years, and 83% if recurrence was later than 5 years 3.…”
Section: Discussionmentioning
confidence: 97%
“…17,19 The procedure can be classified as supralevatory or infralevatory depending on the resection lines in relation to the levator ani muscles. 1 An anterior PE generates a need for urinary deviation, and an infralevatory excision including the removal of the anal canal requires a permanent colostomy.…”
mentioning
confidence: 99%
“…However, improved patient selection, surgical techniques, and perioperative care have resulted in decreased morbidity and potential for long-term survival. 17,21 The objective of this study was to review a singleinstitution experience of PE for patients with recurrent gynecologic malignancy over a decade, in terms of patient and surgical characteristics, complications, recurrences, and survival.…”
mentioning
confidence: 99%